The Study of Pineapple Peel (Ananas comosus L.) Waste Based-Electrolyte Medium: A Simple Experiment Design for the Students - Irvan Maulana Firdaus; Rosiana Dewi Silvia; Ahmad Faqih Amin; Rajwa Vourza Tsaqifa; Ira Purnama; Febiyanto Febiyanto (Department of Chemistry Faculty of Science and Technology Walisongo, 2019)
To promote the student curiosity and understanding in the electrolyte medium was carried out using home-made Volta cell. The electrode materials were iron and carbon for anode (-) and cathode (+), respectively. The experiment was designed by two models that were single-chamber (SC) and three series-packed chambers (3-SCs), respectively. Electrolyte properties could be investigated in pineapple peel (Ananas comosus L.)-based electrolyte medium during the operating time of 8 hours, respectively. The measured-voltage of 2.63 and 2.60 of the 3-SCs system could turn on the LED lamp. However, in this study, the decrease of voltage and current were due to the oxidation process of the pineapple peel-based medium under air, room temperature, and normal pressure during the long-operating time of the experiment. Finally, this research expected to provide additional valuable experience and knowledge as same as to facilitate in information delivering to the students in understanding the electrolyte medium from the waste or natural sources.